2007
DOI: 10.1111/j.1364-3703.2007.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Mining the secretome of the root‐knot nematode Meloidogyne chitwoodi for candidate parasitism genes

Abstract: Parasite proteins secreted at the interface of nematode and host are believed to play an essential role in parasitism. Here, we present an efficient pipeline of bio-informatic algorithms and laboratory experiments to identify candidate parasitism genes within nematode secretomes, i.e. the repertoire of secreted proteins in an organism. We performed our approach on 12 218 expressed sequence tags (ESTs) originating from three life stages of the plant parasitic nematode Meloidogyne chitwoodi--a molecularly unexpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 48 publications
(60 reference statements)
0
49
0
1
Order By: Relevance
“…Several studies using the microaspiration approach identified over 50 different putative secreted parasitism genes from the esophageal glands of root-knot and cyst nematodes (Davis et al 2008 ). In contrast, Roze et al (2008) isolated only eight secreted gland expressed genes after screening more than 12,000 expressed sequence tags (ESTs) generated from whole nematodes (representing three developmental stages). Clearly, a targeted approach can uncover more putative genes involved in parasitism; however, it can be time consuming and require specialized equipment and expertise.…”
Section: Temporal and Spatial Analysis Of Tissues For Gene Expressionmentioning
confidence: 98%
“…Several studies using the microaspiration approach identified over 50 different putative secreted parasitism genes from the esophageal glands of root-knot and cyst nematodes (Davis et al 2008 ). In contrast, Roze et al (2008) isolated only eight secreted gland expressed genes after screening more than 12,000 expressed sequence tags (ESTs) generated from whole nematodes (representing three developmental stages). Clearly, a targeted approach can uncover more putative genes involved in parasitism; however, it can be time consuming and require specialized equipment and expertise.…”
Section: Temporal and Spatial Analysis Of Tissues For Gene Expressionmentioning
confidence: 98%
“…Functional assays of the Gr-EXP1 protein in plant tissues confirmed its expansin-like activity (Qin et al, 2004), representing the first report of an expansin-like protein outside of the plant kingdom. More recently, EST analyses have identified putative expansin-like sequences in several phytoparasitic nematode species including both sedentary and migratory endoparasites (Abad et al, 2008;Haegeman et al, 2009bHaegeman et al, , 2010Kikuchi et al, 2007Kikuchi et al, , 2009Opperman et al, 2008;Roze et al, 2008). The presence of expansin domains in the absence of a CBM has been reported in B. xylophilus and other phytoparasitic nematode species, providing evidence for hypotheses on the evolution of the expansin gene family in nematodes ).…”
Section: ) Non-enzymatic Modification Of Plant Cell Wallsmentioning
confidence: 91%
“…These include the cell wall structure, manipulation of cell fate, protein synthesis and alteration of signaling pathways. Functional tests, using RNAi, have supported the putative role of some of these nematode effectors in pathogenesis (Bellafiore et al 2008;Roze et al 2008;Bellafiore and Briggs 2010).…”
mentioning
confidence: 99%
“…FAR-1 induces susceptibility to RKN through the manipulation of jasmonate-dependent defence response (Iberkleid et al 2013). FAR-1 has also been identified in H. schachtii, M. chitwoodi, M. hapla, M. incognita, P. coffeae and Radopholus similis (Vanholme et al 2006;Bellafiore et al 2008;Jacob et al 2008;Opperman et al 2008;Roze et al 2008;Haegeman et al 2009Haegeman et al , 2011.…”
mentioning
confidence: 99%
See 1 more Smart Citation